2014
DOI: 10.1016/j.apgeochem.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mercury deposition and methylmercury formation in Narraguinnep Reservoir, southwestern Colorado, USA

Abstract: Editorial handling by M. Kersten a b s t r a c t Narraguinnep Reservoir in southwestern Colorado is one of several water bodies in Colorado with a mercury (Hg) advisory as Hg in fish tissue exceed the 0.3 lg/g guideline to protect human health recommended by the State of Colorado. Concentrations of Hg and methyl-Hg were measured in reservoir bottom sediment and pore water extracted from this sediment. Rates of Hg methylation and methylHg demethylation were also measured in reservoir bottom sediment. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Indeed, the genes responsible for Hg-methylation ( hgcAB ) were rarely found in oxygenated layers of the open ocean, suggesting that an unidentified metabolic pathway could be responsible for MeHg production in this environment. In fresh water ecosystems, MeHg formation has been extensively investigated in sediments , and biofilms but rarely in the hypolimnetic waters. , MeHg formed in hypolimnetic waters compartment may actually represent a significant source of MeHg to the food chain when the volume of such water is larger than the volume of surface sediments . Recent studies suggest that atmospheric Hg can be methylated and even accumulated in food chains within 24 h after its deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the genes responsible for Hg-methylation ( hgcAB ) were rarely found in oxygenated layers of the open ocean, suggesting that an unidentified metabolic pathway could be responsible for MeHg production in this environment. In fresh water ecosystems, MeHg formation has been extensively investigated in sediments , and biofilms but rarely in the hypolimnetic waters. , MeHg formed in hypolimnetic waters compartment may actually represent a significant source of MeHg to the food chain when the volume of such water is larger than the volume of surface sediments . Recent studies suggest that atmospheric Hg can be methylated and even accumulated in food chains within 24 h after its deposition.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of an area of continuous permafrost and interstitial tundra at BEO, Barrow, Alaska, showed MeHg concentrations ranging 0.3 to 2.3 ng L -1 in ponded surface water and active layer soil pore waters (Table S2), which is more than 10 times higher than those typically found in uncontaminated soils and sediments at lower latitudes (Gray et al, 2014). The respective total Hg and MeHg concentrations per gram dry weight soil in the core sample before incubation were 55.2 ± 1.3 and 0.08 ± 0.01 ng in the organic layer, and 54.0 ± 1.2 and 0.07± 0.01 ng in the mineral layer.…”
Section: Resultsmentioning
confidence: 99%
“…The MeHg/THg ratio in this compilation was generally low across the landscape with a median value of 0.7% and a 90 th percentile of 3.1%, although more than 100 locations exceeded the 6% benchmark (Figure 4b). Several other studies have reported similar central tendencies for MeHg/THg ratios: estuarine sediment in southern Florida (0.8%, Kannan et al, 1998), estuarine sites in New England (0.4%, Taylor et al, 2012), reservoirs in Colorado (0.2% to 0.3%, Gray et al, 2014), and mine-dominated large-scale watersheds in the USA (1%, Krabbenhoft et al, 1999). However, much higher mean MeHg/THg ratios were reported in northeastern lakes and streams (4%, Loukmas et al, 2006) and watersheds across the USA (3.2%, Scudder et al, 2009), particularly in mixed agricultural-forested watersheds (10%, Krabbenhoft et al, 1999).…”
Section: Methylmercurymentioning
confidence: 52%